2020
DOI: 10.3390/molecules25235701
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity and Barrier Properties against UV Radiation of Alkaline and Enzymatically Treated Linen Woven Fabrics Coated with Inorganic Hybrid Material

Abstract: One of the directions of development in the textiles industry is the search for new technologies for producing modern multifunctional products. New solutions are sought to obtain materials that will protect humans against the harmful effects of the environment, including such factors as the activity of microorganisms and UV radiation. Products made of natural cellulose fibers are often used. In the case of this type of material, it is very important to perform appropriate pretreatment before subsequent technol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Thus, it has been observed that polyester fabrics had a higher protection factor than cotton [55]. At the same time, different types of coatings were made using modern methods, using absorbers or blockers to improve the anti-UV properties [56][57][58][59][60].…”
Section: Sun Protective Performances Evaluationmentioning
confidence: 99%
“…Thus, it has been observed that polyester fabrics had a higher protection factor than cotton [55]. At the same time, different types of coatings were made using modern methods, using absorbers or blockers to improve the anti-UV properties [56][57][58][59][60].…”
Section: Sun Protective Performances Evaluationmentioning
confidence: 99%
“…The UV protection capacity obtained was also very interesting, with UPF values of >40. The developed samples showed special potential to be used as clothing or outdoor textiles, since they offer protection against microorganisms and UV radiation [ 11 ].…”
Section: Fibrous Structures Functionalized With Nanomaterialsmentioning
confidence: 99%
“…of CuO-SiO 2 , ( e , f ) linen fabric after enzymatic treatment with 5.0 U/g of laccase and dip-coating with 5% wt. of CuO-SiO 2 [ 11 ].…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Antimicrobial modifications of textile materials [ 16 ], and their protection against UV radiation with different kinds of modifiers [ 17 ], were also very often applied.…”
Section: Introductionmentioning
confidence: 99%